Effect of chromium on growth rates of algae in mono- and mixed cultures (Experimental biology, 2016)
The publication was to identify the main indicators of growth and development of cell cultures of microalgae. In algocenosis seasonal succession, accompanied by the change of the dominant species, are not fully understood phenomenon. In additional study of interspecies interaction in the presence of damaging factors may contribute to clarify the direction of growth processes in algocenosis.The study determined the growth rates of cell cultures and dry and wet biomass on growth parameters and cell concentration.In this regard, the microalgae is a test object to determine the contaminated wastewater and monitoring to detect toxicity reservoirs. To determine the toxic effect of concentrates was introduced into an aqueous environment potassium dichromate.
Keywords: microalgae; chromium; stability; growth rate; biomass; allelopathy; algoflora; antagonism